'What are you crying for? I don't even know you' – The experiences of teenagers communicating with their peers when returning to school. (April 2019) - Pini, Simon; Hugh-Jones, Siobhan; Shearsmith, Leanne; Gardner, Peter
Abstract : Purpose: Young people (YP) returning to school after a cancer diagnosis and treatment have to decide who has the right to know about their cancer experiences and how to distribute this information to peers. Young people face unique challenges in this area because of their life stage, their need to reintegrate with peers, and their own approach to their disease and treatment. This paper explores the perspectives of young people as they return to school during and after curative cancer treatment. Method: 12 young people (6 females, 6 males) from the north of England (aged 13–16 years at time of recruitment) took part in photo elicitation interviews conducted at three time points during the year following a diagnosis of lymphoma, Hodgkin's lymphoma, osteosarcoma, A-plastic anaemia or acute lymphoblastic leukaemia. Interviews were transcribed and analysed using Interpretative Phenomenological Analysis (IPA). Results: Three main themes emerged: 'approaches to telling', 'lives becoming public property'; and 'owning the story'. Within these themes participants experienced stressors related to altered peer group dynamics, being propelled into the foreground of the school environment, being responsible for the feelings and needs of others, and conflicts between their perception of coping and the reactions of others. Conclusions: Re-entering school following a diagnosis of cancer can result in challenging dynamics for a young person, which they are not always equipped to manage. Participants displayed individual differences in their approaches and preferences, but inevitably all had to cope with their lives becoming public property and managing the narrative of their cancer experience. Highlights: Participants described "telling" as an ongoing dynamic process marked by multiple school visits throughout their treatment. Changes to their appearance, mobility and abilities propelled YAs into the foreground and invited questions from peers. Having the attention of many distant peers in school was a challenge to participants' desire for normality. Sometimes questioning from peers on their return to school highlighted the limitations of their knowledge about their cancer. Providing a knowledgeable and confident narrative allowed participants to reinforce the belief that they will survive cancer.